Enhancing the strength and transparency of egg white gels: mechanistic insights into the role of sodium decanoate - Yuting Du; Xuan Yao; Qianying Ding; Gan Hu; Chunmei Wang; Yizi Yuan; Zhifeng Zhao; Fang Geng (Food Science of Animal Products)
This paper evaluates the effect of sodium decanoate (C10) on improving the strength and transparency mechanism of heat-induced egg white gel (HEW-G). The effect of C10 on the strength and transparency of egg white gels was investigated by measuring gel transparency, texture, rheology, water-holding properties, and scanning electron microscopy observation. The findings demonstrated that the addition of C10 initially enhanced and then reduced the gel strength, while consistently increasing transparency. C10 promotes the formation of smooth and dense gel network structure mainly by enhancing the hydrophobic interactions of egg white protein (EWP), thus effectively improving the gel properties. The microstructure observation showed that C10 promoted protein aggregation and the formation of a dense network. When the addition of C10 was 2% (V/V), the network became looser. Transmission electron microscopy and infrared spectroscopy analyses revealed that C10’s hydrophobic nature facilitated interactions with EWP, strengthening hydrophobic associations and forming a stable three-dimensional network. This process markedly enhanced the mechanical strength and transparency of EWP. For example, comparing with HEW-G, the hardness of 0.5% (V/V) sodium decanoate egg white heat-induced gel (SCHEW1-G) was increased by 129.25%, the elasticity of SCHEW1-G was increased by 10.59%, the chewiness was increased by 351.44%, and the light transmission was increased by 150.50%. As a functional ingredient, C10 can improve the texture, nutritional value, and stability of food, promoting its wide range of high-value applications in food. As a functional ingredient, C10 can improve the texture, nutritional value and stability of food, promoting its wide range of high-value applications in food.